Commercial fisheries of Panay Gulf. - Magugat, Francisco G. (College of Fisheries, University of the Philippines, 1951)
This report is intended to disseminate information relating to the fishing industry in Panay Gulf. It conatains information gathered during my 4 months intensive practice in fishing ground from Aguisan, Himamaylan, Negros Occidental to Southern part of Guimaras Islands. From the information gathered this fishing ground is rich with fishery resources specially so if illegal fishing is entirely eradicated if not minimized.